Eleven new species of the spider genus Althepus Thorell, 1898 (Araneae, Ochyroceratidae) from Thailand - Liu, Chang; Li, Fengyuan; Wongprom, Prasit; Zheng, Guo; Li, Shuqiang (Zootaxa, 2017)
Eleven new Althepus species of the spider family Ochyroceratidae are reported from Thailand: A. duan sp. nov., A. duoji sp. nov. (male only), A. huoyan sp. nov., A. jiandan sp. nov., A. kuan sp. nov., A. lakmueangensis sp. nov., A. languensis sp. nov., A. muangensis sp. nov., A. qiqiu sp. nov. (female only), A. tuqi sp. nov., A. xianxi sp. nov. All types are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing, China (IZCAS).